A rapid onset of ocean acidification associated with the end-Permian mass extinction - Li, Rucao; Wu, Nanping; Shen, Shu-Zhong; Wang, Xiao-Lei; Chen, Huayong; Algeo, Thomas J.; Zhang, Hua; Zhang, Feifei (Global and Planetary Change, 2023)
The end-Permian mass extinction (EPME) resulted in the most severe biodiversity loss in Earth's history, the cause(s) of which are still heavily debated. Recent studies have emphasized the role of ocean acidification on marine ecosystem collapse during the EPME, but the timing of the onset of ocean acidification and its relationship to contemporaneous large igneous province (LIP) magmatism remain ambiguous. Here, we present the first in-situ secondary ion mass spectrometry (SIMS) sulfur isotope data for pyrite and marcasite from the Meishan section, which hosts the Global Stratotype Section and Point (GSSP) of the Permian-Triassic boundary (PTB). We found a sharp increase in marcasite abundance and a concurrent decrease in marcasite delta 34S to highly negative values (ca. -50 parts per thousand) within the EPME interval (i.e., Beds 25-28). Combined with the morphology of marcasite, we infer that the formation of 34S-depleted anhedral marcasite occurred in a sulfate-unlimited porewater environment that was likely well connected to the overlying water column. A similar negative shift in delta 34Smarcasite was observed in the EPME interval of the Penglaitan section. Given that marcasite forms only in acidic conditions and low delta 34Smarcasite values suggest an open porewater system, the sharp negative shift in the delta 34S of syndepositional marcasite records a sudden acidification of Late Permian seawater. This conclusion is broadly consistent with previously reported boron isotope data of brachiopod-shell which witnessed a negative shift at the same stratigraphic horizons. While the ocean acidification event started after the starting point (base of Bed 25) of EPME, it occurred broadly within the extinction interval (Beds 25 to 28), supporting the hypothesis that ocean acidification may have been a major environmental factor contributing to the end-Permian marine ecosystem collapse.